(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
In this article, 35XGCL steel alloy was liquidized. The resulting liquid metal is cleaned of non – metallic inclusions and gas pores by aluminum alloying, and casting technology was developed based on energy and resource efficient innovative technologies. In order to obtain a high – quality cast product, the composition of sand – clay and liquid glass mold mixtures was developed, and a high – quality cast product was liquefied. In addition, thermal treatment regimes were developed to increase the mechanical properties of the cast alloy, and as a result, a high – quality and resource – efficient cast product was obtained.